Antiperoxynitrite Treatment Ameliorates Vasorelaxation of Resistance Arteries in Aging Rats: Involvement With Protection of Circulating Endothelial Progenitor Cells. Issue 5 (November 2016) - Sun, Qi; Dong, Yu; Wang, Huanyuan; Jiao, Kun; Xu, Jiahui; Ma, Lu; Huang, Haixia; Liu, Huirong; Wang, Wen
Abstract : Abstract: Numerous studies have found that the age-associated structural and functional alterations in arteries were characterized by increased endothelial dysfunction. In this study, young (3 months), adult (9 months), and aging (20 months) male Sprague-Dawley rats were randomly divided into 6 groups, including control groups and FeTMPyP (peroxynitrite scavenger) groups receiving saline and FeTMPyP, respectively, for 5 administrations once every 3 days through intraperitoneal injection. The aged-related proteins beta-galactosidase, p53, and p16 as well as the nitrotyrosine and endothelial marker endothelial nitric oxide synthase and von Willebrand factor (vWF) in vascular tissues were measured by immunohistochemistry. Endothelium-dependent vasorelaxation and endothelium-independent vasorelaxation of rat thoracic aortas and mesenteric arteries were measured by acetylcholine and sodium nitroprusside, respectively. The amount of circulating endothelial progenitor cells (EPCs) was determined by flow cytometry. The endothelium-dependent/independent relaxation in mesenteric arteries and the amount of circulating EPCs (CD31 + /CD34 + ) in peripheral blood of aging rats were reduced significantly compared with young and adult rats. Immunohistochemistry results showed that the nitrotyrosine levels and morphological damage in mesenteric arteries were increased significantly in aging rats. Adoption of peroxynitrite scavenger FeTMPyP intervention may not only improve the endothelium-dependent relaxation and the amount of circulating EPCs in aging rats but also reverse endothelial injury. In conclusion, this study demonstrates that enhanced nitrative stress may aggravate the endothelial injury and vascular dysfunction of resistance arteries in aging rats. Antiperoxynitrite treatment can ameliorate the vasorelaxation and may be involved with the protection of circulating EPCs.